Ghana : 2005 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criteria and Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that economic performance in Ghana has improved since 2000, with the economy growing at its fastest pace in more than a decade. In 2004, real GDP growth reached 5.8 percent, driven by agriculture and a strong pickup in the services and construction sectors-helped by increased bank credit and private inward remittances. Ghana's medium-term prospects appear promising, with growth projected to continue at the current relatively high rate, provided that macroeconomic stability becomes further entrenched with fiscal sustainability, inflation declines further, and the government perseveres with structural reform.